Laparoscopic Sleeve Gastrectomy for Mildly Obese Patients (Body Mass Index of 30 <35 kg/m2): Operative Outcome and Short-Term Results - Roger Noun; Ghassan Chakhtoura; Marwan Nasr; Judith Skaff; Naîm Choucair; Nathalie Rkaybi; Carla Tohme-Noun (Journal of Obesity)
Background. Data concerning laparoscopic sleeve gastrectomy (LSG) in mild obesity are under investigation. Aim/Objective. May 2010 to May 2012, 122 consecutive patients with preoperative body mass index (BMI) of 33±2.5 kg/m2 (range 30–34.9) undergoing LSG were studied. Mean age was 33±10 years (range 15–60), and 105 (86%) were women. Mean preoperative weight was 91±9.7 kg (range 66–121), and preoperative excess weight was 30±6.7 kg (range 19–43). Comorbidities were detected in 44 (36%) patients. Results. Mean operative time was 58±15 min (range 40–95), and postoperative stay was 1.8±0.19 days (range 1.5–3). There were no admissions to intensive care unit and no deaths within 30 days of surgery. The rates of leaks and strictures were 0%, and of hemorrhage 1.6%. At 12 months, BMI decreased to 24.7±2, and the percentage of excess weight loss (% EWL) reached 76.5%. None of the patients had a BMI below 20 kg/m2. Comorbidities resolved in 70.5% or improved in 29.5%. Patient satisfaction scoring (1–5) at least 1 year after was 4.6±0.8 for body image and 4.4±0.6 for food tolerance. Conclusion. LSG for mildly obese patients has proved to be technically relatively easy, safe, and benefic in the short term.